A unique case of de novo 5q33.3–q34 triplication with uniparental isodisomy of 5q34–qter. Issue 8 (4th July 2013) - Fujita, Atsushi; Suzumura, Hiroshi; Nakashima, Mitsuko; Tsurusaki, Yoshinori; Saitsu, Hirotomo; Harada, Naoki; Matsumoto, Naomichi; Miyake, Noriko
Abstract De novo triplication together with uniparental disomy (UPD) is a rare genomic rearrangement, and, to our knowledge, co‐occurrence has previously only been reported in two individuals. We encountered a patient with a suspected karyotype of 46, XX, del(5)(q33.1q33.3), dup(5)(q31.3q33.3) or (q33.1q35.1). Genetic analysis revealed tetrasomy of 5q33.3–q34 caused by de novo middle inverted triplication and uniparental isodisomy of 5q34–qter. Most clinical features in the patient were observed in previously reported cases of duplication overlapping with 5q33.3–q34, with the exception of hearing loss. The FOXI1 gene, which causes autosomal recessive deafness (OMIM 600791, DFNB4) when mutated, was contained within the uniparental isodisomy region (5q34–qter). However, no mutations were identified following Sanger sequencing of FOXI1. This is the first report of a patient with de novo triplication together with uniparental isodisomy of chromosome 5q. As segmental isodisomy is a post‐fertilization error, it is thought to have occurred during mitosis just after fertilization via a U‐type exchange, while inverted duplication could have occurred during meiosis or mitosis. This study reaffirms that the single nucleotide polymorphism (SNP) array is a powerful tool to screen for UPD in a single experiment, especially in cases of isodisomy. © 2013 Wiley Periodicals, Inc.